KEPEMILIKAN SAHAM PUBLIK, KINERJA LINGKUNGAN DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Ristiyani Mina; Darlis Edfan; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of public share ownership, environmental performance, and firm size on the disclosure of corporate social responsibility. The variables of this study consist of public share ownership, environmental performance and firm size as independent variables, and disclosure of corporate social responsibility as the dependent variable. The research sample consisted of 13 food and beverage companies listed on the Indonesia Stock Exchange (IDX) 2018-2020. The method used in this research is multiple linear regression analysis method. While the sampling technique using purposive sampling technique is taking samples using the criteria that have been set by the researcher. The results show that public share ownership, environmental performance, and firm size have a positive effect on the disclosure of corporate social responsibility.Keywords: Public share ownership, environmental performance, firm size and disclosure of social responsibility